Research hotspots and trends of amblyopia treatment from 2015 to 2025: a bibliometric analysis - Zhou, Chenyan; Li, Xiaoru; Luo, Xiaoliang; Song, Shuning; Wang, Lvchun; Huang, Junpeng; Zhang, Xiaobing; Liu, Die; Chai, Yong; Zhou, Jiawei (Frontiers in Neuroscience, 2026)
BackgroundThis study aims to provide a comprehensive view of the current research status, hotspots, and emerging trends of amblyopia treatment through bibliometric analysis of published literature.MethodsWe retrieved publications from the Web of Science Core Collection (WoSCC) and PubMed databases from 2015 to 2025. CiteSpace was used to analyze and visualize countries, institutions, journals, keywords, and references.ResultsThe analysis included 514 publications that show a steady increasing trend. The United States and China are the most productive countries. McGill University has made notable contributions to this field. The most prolific journal is the Journal of AAPOS, while high-impact journal JAMA Ophthalmology has the highest citations. Keyword and reference analyses reveal that the research focus has shifted to clinical trials and various binocular treatments. The analyses of the recent citation burst and clinical trials reflect the future trend of amblyopia treatment towards personalized and technologically optimized treatment and the validation of novel neuromodulation therapies.ConclusionThis study reveals the current hotspots and future directions of amblyopia treatment research. Current research focuses on clinical trials of binocular treatment through different digital platforms in amblyopia. Our findings provide critical insights for scientific and clinical research on amblyopia treatment.